Tantangan Guru Dalam Pembelajaran Di Kelas Rendah Di SD Negeri 5 Nongan - I Wayan Numertayasa; Ni Kadek Wulan Citrawati (Dharmas Education Journal (DE_Journal), 2026)
This study aims to describe the challenges faced by teachers in lower-grade learning at SD Negeri 5 Nongan. The research employs a qualitative descriptive approach with 5 third-grade students as subjects, and data were collected through interviews and observations. Data analysis was conducted descriptively. Findings indicate that teachers encounter difficulties such as low student concentration and motivation, differences in reading and writing skills, and limited teaching resources and media. To address these challenges, teachers apply persuasive approaches, concrete media and educational games, as well as active and enjoyable learning methods, adapted to students’ concrete operational development stage. The study emphasizes the importance of teachers’ ability to manage classrooms, adjust strategies, and innovate in media use to enhance learning outcomes. These findings are expected to serve as a reference for teachers and schools to improve learning effectiveness in lower grades.